Hydathode structure and localization in Pteris vittata fronds and evidence for their involvement in arsenic leaching. (1st November 2016) - Cantamessa, S.; D'agostino, G.; Berta, G.
Abstract : Pteris vittata, a fern able to hyperaccumulate arsenic (As) in its fronds, has been object of a number of studies aimed to understand the mechanisms involved in As absorption and tolerance. This study has focused on a new mechanism, As leaching, already observed in P. vittata, but not explained, based on the possible involvement of hydathodes, not yet described in this fern; moreover, the results contained in this article will provide information on a more detailed frond anatomy of P. vittata . A combination of light and electron microscopic techniques (transmission electron microscopy and environmental scanning electron microscopy with energy dispersive X-ray) and chemical analyses (inductively coupled plasma atomic emission spectroscopy) was used. The results suggest that in phytoremediation processes under field conditions there could be the need to know the atmospheric conditions before harvesting plants, to avoid the loss of As in the environment.